MERIDIONAL DISTRIBUTION OF SHORT-VERTICAL-SCALE FLUCTUATIONS IN THE LOWER STRATOSPHERE REVEALED BY CROSS-EQUATORIAL OZONESONDE OBSERVATIONS ON "SHIRASE" - オギノ, シンヤ; ヤマナカ, マナブ; カネト, ススム; ヤマノウチ, タカシ; フカオ, ショウイチロウ; OGINO, Shin-Ya; YAMANAKA, Manabu D.; KANETO, Susumu; YAMANOUCHI, Takashi; FUKAO, Shoichiro (National Institute of Polar Research, 1997)
P(論文) Meridional distribution of magnitude for short-vertical-scale fluctuations in the lower stratosphere over the wide latitudinal region between 62°S-43°N roughly along 120°E is investigated on the basis of vertical wavenumber spectra analyzed from temperature and ozone mixing ratio data observed by ozonesondes on "SHIRASE" cruises from 1987 to 1990. The power spectral densities of the 4.0km, 2.7km and 2.0km wavelength components for normalized temperature and normalized ozone mixing ratio in the altitude range of 19-27km are plotted as functions of latitude. It is found that there are symmetrical distributions with maxima near the equator as the first component and asymmetrical ones with larger value in the Northern Hemisphere as the second component for power spectral densities of normalized temperature. However, similar features are not found in distributions of ozone mixing ratio. To investigate this inconsistency, detailed short-vertical-scale structures of potential temperature and ozone mixing ratio have been compared. It is found that they do not show good agreement in the mid-latitude region. departmental bulletin paper